1992
DOI: 10.1007/bf00169100
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of antioxidants and age-related macular degeneration

Abstract: A number of reports have suggested that oxidative damage in the retina may contribute to the pathogenesis of Age-related macular degeneration (AMD). The present study was designed to investigate the hypothesis that serum levels of the antioxidants, Vitamin E and selenium are related to the pathogenesis of AMD. Fasting bloods were obtained from 80 patients with AMD and 86 controls. Assays for serum levels of Vitamin E, selenium, cholesterol and triglycerides were performed. Assessment of patients and controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Some studies have found an increased risk of AMD with a past cardiovascular event [30,31], systemic hypertension [17,21,32] and increased blood cholesterol levels [11,23], although other studies have found no association with vascular events [19,23,33], systemic hypertension [19,23,33,34] or blood lipid levels [19][20][21][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found an increased risk of AMD with a past cardiovascular event [30,31], systemic hypertension [17,21,32] and increased blood cholesterol levels [11,23], although other studies have found no association with vascular events [19,23,33], systemic hypertension [19,23,33,34] or blood lipid levels [19][20][21][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…It is also hypothesized to be able to protect the macula against oxidative damage. However, these results have not been convincing and were inconclusive [47,68].…”
Section: Mineralsmentioning
confidence: 99%
“…In 1992, the Eye Disease Case Control Study Group, reported a significant 4-fold increased risk for exudative AMD with the highest serum cholesterol concentration [39]. Since then, only five studies reported a significant increased risk of AMD with high level of total cholesterol [23], [33], [40]–[42], while 13 reported no significant association [26], [27], [30], [32], [34][38], [43][46], and two an inverse relationship [47], [48].…”
Section: Introductionmentioning
confidence: 99%